Talak Ba'in Sughra Maslahah Perspective in Malaysia and Border Communities in Sambas, West Kalimantan Indonesia - Asman; Asmak Ab Rahman (Indonesian Journal of Law and Islamic Law (IJLIL), 2024)
This research discusses the legal claims of wives to husbands Ma?hla?ah perspective on the border communities of Indonesia-Malaysia sambas West Kalimantan. This study was based on ma?hla?ah al-?haruriy?h, ma?hla?ah tahsiniyah and ma?hla?ah hajiyah. According to the school of Imam Shafi'i talaq ba'in shughra is also called khulu' where the husband is not allowed to reconcile with the wife during the period of iddah and the husband needs a new marriage contract in order to return to the wife who has mentalized with ba'in shughra. In order for this research to be directed and systematic, the subject matter is developed in the research question, namely: What is the benefit aspect of the wife's lawsuit to the husband from the perspective of ma?hla?ah? This type of qualitative research is field research with an Islamic legal approach. The informant in this study is the Malay Sambas community who are divorce perpetrators. Based on the results of the research obtained, that the causes of talaq ba'in shughra in Sambas based on data obtained from  the Malay Sambas community are, household economic problems so that the wife so that the wife is not fulfilled her rights, electrocution and continuous quarrels so that the wife cannot stand the situation and the husband leaves his wife and children for no reason so that there is no news so that the wife feels no Note.  with the talaq ba'in sugra there will be an element of harm for divorced couples in the Indonesian-Malaysian border communities, such as, it will disrupt the harmony of the family, and the husband cannot return to his ex-wife because the talaq bain sughra continues.